An Exploratory Study to Develop a Geotourism Typology Model. (27th June 2013) - Hurtado, Hasoly; Dowling, Ross; Sanders, Dale
ABSTRACT This paper offers a starting point to the development of a future geotourism typology model through the adaptation of McKercher's (2002) cultural tourism typology model. This approach is tested by surveying visitors from Crystal Cave in Yanchep National Park, Western Australia. The results indicate a need to include some new elements and adapt some of the existing cultural tourism typologies to fit the geotourism context. Copyright © 2013 John Wiley & Sons, Ltd.